2017
DOI: 10.3390/galaxies5040066
|View full text |Cite
|
Sign up to set email alerts
|

Radio Polarisation Study of High Rotation Measure AGNs

Abstract: As radio polarised emission from astrophysical objects traverse through foreground magnetised plasma, the physical conditions along the lines of sight are encrypted in the form of rotation measure (RM). We performed broadband spectro-polarimetric observations of high rotation measure (|RM| 300 rad m −2 ) sources away from the Galactic plane (|b| > 10 • ) selected from the NVSS RM catalogue. The main goals are to verify the NVSS RM values, which could be susceptible to nπ-ambiguity, as well as to identify the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Faraday rotation in a magneto-ionic medium produces various external or internal depolarization processes (e.g., Burn 1966;Tribble 1991;Sokoloff et al 1998). These provide a unique and critical diagnostic of the magneto-ionic medium, but only when observed over a wide frequency range with nearcontinuous frequency coverage (e.g., O'Sullivan et al 2012;Anderson et al 2016;Ma et al 2017;Pasetto et al 2018, Figure 3). Until a few years ago, polarimetric studies have either relied on a small number of widely spaced narrow bands, or have observed over a continuous but relatively narrow (∼10%) fractional bandwidth.…”
Section: Polarization In Vlassmentioning
confidence: 99%
“…Faraday rotation in a magneto-ionic medium produces various external or internal depolarization processes (e.g., Burn 1966;Tribble 1991;Sokoloff et al 1998). These provide a unique and critical diagnostic of the magneto-ionic medium, but only when observed over a wide frequency range with nearcontinuous frequency coverage (e.g., O'Sullivan et al 2012;Anderson et al 2016;Ma et al 2017;Pasetto et al 2018, Figure 3). Until a few years ago, polarimetric studies have either relied on a small number of widely spaced narrow bands, or have observed over a continuous but relatively narrow (∼10%) fractional bandwidth.…”
Section: Polarization In Vlassmentioning
confidence: 99%
“…They could have been detected with S-PASS/ATCA, and also with TSS09. However, in TSS09, such sources suffer from strong depolarization (see figure 1 in the paper by Taylor et al, Stil &Taylor 2007, andPasetto et al 2016) and they can be misinterpreted because of nπ ambiguities in polarization angle (see, e.g., Ma et al 2017). In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, Φ is determined by observing ψ at a few wavelengths and fitting a linear relationship as a function of λ 2 . This method suffers from a number of problems including nπ ambiguities and being constrained to high signal-to-noise (S/N) polarization observations (Ma et al 2017). This is especially true when Φ is large as Q and U must be measured in narrow channels.…”
Section: Rm Synthesismentioning
confidence: 99%